Search for production of invisible final states in single-photon decays of Υ(1S) - Amo Sanchez, Pablo del; Marks, Jörg; Uwer, Ulrich (Physical review letters, 2011)
We search for single-photon decays of the Υ(1S) resonance, Υ→γ+invisible, where the invisible state is either a particle of definite mass, such as a light Higgs boson A0, or a pair of dark matter particles, χ¯¯¯χ. Both A0 and χ are assumed to have zero spin. We tag Υ(1S) decays with a dipion transition Υ(2S)→π+π−Υ(1S) and look for events with a single energetic photon and significant missing energy. We find no evidence for such processes in the mass range mA0≤9.2 GeV and mχ≤4.5 GeV in the sample of 98×106 Υ(2S) decays collected with the BABAR detector and set stringent limits on new physics models that contain light dark matter states.
*BABAR Collaboration: P. del Amo Sanchez, J. Marks, U. Uwer [und 436 weitere Personen]
Gesehen am 04.10.2022